Genetic Variants Modify Susceptibility to Leukemia in Infants: A Children’s Oncology Group Report - Ross, Julie A. (2012)
BACKGROUND: The mixed lineage leukemia (MLL) gene is commonly rearranged in infant leukemia (IL). Genetic determinants of susceptibility to IL are unknown. Recent genome wide association studies for childhood acute lymphoblastic leukemia (ALL) have identified susceptibility loci at IKZF1, ARID5B, and CEBPE. PROCEDURE: We genotyped these loci in 171 infants with leukemia and 384 controls and evaluated associations overall, by subtype (ALL, acute myeloid leukemia (AML)), and by presence (+) or absence (−) of MLL rearrangements. RESULTS: Homozygosity for a variant IKZF1 allele (rs11978267) increased risk of infant AML (Odds Ratio (OR)=3.9, 95% Confidence Interval (CI)=1.8–8.4); the increased risk was similar for AML/MLL+ and MLL− cases. In contrast, risk of ALL/MLL− was increased in infants homozygous for the IKZF1 variant (OR=5.1, 95%CI=1.8–14.5) but the variant did not modify risk of ALL/MLL+. For ARID5B (rs10821936), homozygosity for the variant allele increased risk for the ALL/MLL− subgroup only (OR=7.2, 95%CI=2.5–20.6). There was little evidence of an association with the CEBP variant (rs2239633). CONCLUSION: IKZF1 is expressed in early hematopoiesis, including precursor myeloid cells. Our data provide the first evidence that IKZF1 modifies susceptibility to infant AML, irrespective of MLL rearrangements, and could provide important new etiologic insights into this rare and heterogeneous hematopoietic malignancy.